(untitled) (Cultura Económica, 2019)
The Spanish university professor Josep M. Bricall analyses in this article the situation of education and research in the university, emphasizing its place in society and its issues. The current technological and market contexts modify and organize education and the objectives of the students that choose an education in the university. It is required to produce, use and divulge knowledge at the same time, establishing new relationships between the university and its context. Bricall offers a positive view of these changes, presenting the new circumstances as new opportunities and enriching challenges.